2006
DOI: 10.1158/1055-9965.epi-06-0010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of p53 in Barrett's Esophagus

Abstract: Barrett's esophagus is an established precursor to esophageal adenocarcinoma. Whereas most patients with Barrett's esophagus do not progress to adenocarcinoma, patients with progression have a poor prognosis. Current management strategies use frequent endoscopic surveillance and multiple nontargeted biopsies. This approach, however, may miss dysplastic areas. Furthermore, given the relatively high prevalence of Barrett's esophagus but low incidence of progression, this invasive and expensive approach has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…Our findings are consistent with a previous study that suggested that fewer than 5% of patients with adenocarcinoma of the esophagus have known BE prior to the diagnosis of adenocarcinoma [19]. Recent studies regarding testing with biomarkers may hold promise for the future [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with a previous study that suggested that fewer than 5% of patients with adenocarcinoma of the esophagus have known BE prior to the diagnosis of adenocarcinoma [19]. Recent studies regarding testing with biomarkers may hold promise for the future [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…These cell lines are useful in that one is wild-type p53 (SEG1) while the other is mutated (BIC-1). p53 mutation has been associated with Barrett's aggressiveness, and may be an early stage in the transformation of benign to malignant epithelium (26). This data in conjunction with the other studies cited above indicates that IP6 may have the potential to become an effective adjuvant treatment for Barrett's adenocarcinoma.…”
Section: Discussionsupporting
confidence: 55%
“…TP53 was found to have a low sensitivity, but p53 mutational status may ultimately be a component of such a molecular marker panel. 4,20 C-erbB2/Her-2/neu could not be demonstrated as a molecular marker by Langer et al 18 but fluorescence in situ hybridization (FISH) analysis demonstrated amplification/overexpression of Her-2/neu as a marker of progression from Barrett's epithelium to dysplasia. 22 The authors suggested that FISH represents a useful diagnostic tool for selecting patients for more targeted therapeutic approaches.…”
Section: Ink4amentioning
confidence: 99%
“…3 Although most patients with Barrett's esophagus do not progress to adenocarcinoma, those with progression have a poor prognosis. 4 Endoscopic resection has been recommended as a local curative approach for (unicentric) mucosal Barrett's adenocarcinoma (m1 or m2, and m3 without lymph vessel infiltration). 5 Surgery is still the therapy of choice in early Barrett's adenocarcinoma infiltrating submucosal layers or poorly differentiated tumors because of a higher risk of lymph-node metastasis.…”
mentioning
confidence: 99%